2020
DOI: 10.3390/ijms21061943
|View full text |Cite
|
Sign up to set email alerts
|

Integrated miRNA/mRNA Counter-Expression Analysis Highlights Oxidative Stress-Related Genes CCR7 and FOXO1 as Blood Markers of Coronary Arterial Disease

Abstract: Our interest in the mechanisms of atherosclerosis progression (ATHp) has led to the recent identification of 13 miRNAs and 1285 mRNAs whose expression was altered during ATHp. Here, we deepen the functional relationship among these 13 miRNAs and genes associated to oxidative stress, a crucial step in the onset and progression of vascular disease. We first compiled a list of genes associated to the response to oxidative stress (Oxstress genes) by performing a reverse Gene Ontology analysis (rGO, from the GO ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…A recent study by Hueso et al [ 32 ] reported downregulation of FOXO1 gene expression in patients with stable CAD. Subjects in this study ( n = 10 with) were undergoing scheduled CABG surgery.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Hueso et al [ 32 ] reported downregulation of FOXO1 gene expression in patients with stable CAD. Subjects in this study ( n = 10 with) were undergoing scheduled CABG surgery.…”
Section: Discussionmentioning
confidence: 99%
“…These miRNAs regulate the VSMC differentiation and coronary AS mainly through the modulation of target gene expression [ 3 , 25 , 26 ]. Previous studies have reported several miRNA-mRNA regulatory networks in AS [ 27 - 29 ]. For instance, upregulated miR-93 contributes to coronary AS pathogenesis through targeting ABCA1 [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Though terminal-exhausted CD8 + T cells express high levels of PD-1 during chronic infections, there is a possibility of re-invigorating the PD-1 high CD8 + T cells into an effector phase from a terminal differentiation state through FoxO1 that is accumulated in the nucleus [108]. Very recently, it was also shown that FoxO1 gene polymorphisms have been associated with the development of carotid atherosclerosis and were reported to be downregulated in coronary heart disease patients [186]. Not only this, FoxO1 might also function as a critical component for protecting PD-1 high CD8 + T cells from apoptosis, by increasing their survival through Bcl 2 upregulation.…”
Section: Role Of Pd-1/pd-l1 Axis In Helicobacter-associated Atherosclmentioning
confidence: 99%